Pengaruh Digital Marketing terhadap Kepuasan Konsumen Bisnis Fashion - Anjelina Dewi, Natasya (Asosiasi Ahli Administrasi Indonesia, 2024)
This study aims to analyze the influence of digital marketing on consumer satisfaction in the fashion business. Respondents as many as 120 students from various regions in Bandung Raya, Indonesia participated in this study. The research method used is a quantitative approach to analyze respondent data, and a descriptive survey was used. Data were collected through a questionnaire that evaluated students' understanding of digital marketing and their level of satisfaction with online fashion businesses. The results of a simple regression analysis showed a significant influence of digital marketing on consumer satisfaction, with a coefficient of determination of 55.8%. This study provides insight that digital marketing plays a crucial role in influencing consumer satisfaction in the fashion business, especially among students. The practical implications of these findings can help fashion companies optimize their digital marketing strategies.